2021
DOI: 10.1152/ajpheart.00538.2020
|View full text |Cite
|
Sign up to set email alerts
|

Pygo1 regulates pathological cardiac hypertrophy via a β-catenin-dependent mechanism

Abstract: Wnt/β-catenin signalling plays a key role in pathological cardiac remodelling in adults. The identification of a tissue-specific Wnt/β-catenin interaction factor may realise a tissue-specific clinical targeting strategy. Drosophila Pygo codes for the core interaction factor of Wnt/β-catenin. Two Pygo homologs, Pygo1 and Pygo2, have been identified in mammals. Different from the ubiquitous expression profile of Pygo2, Pygo1is enriched in cardiac tissue. However, the role of Pygo1 in mammalian cardiac disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The in vivo silencing of Pygo1 also attenuates the development of isoproterenol-induced heart hypertrophy. 187 More evidence of the hypertrophic action of βcatenin comes from Dvl-1-overexpressing and αEcatenin knockout mice. In both cases, levels of active βcatenin increased because of liberation from the destruction complex and adherens junction, respectively.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo silencing of Pygo1 also attenuates the development of isoproterenol-induced heart hypertrophy. 187 More evidence of the hypertrophic action of βcatenin comes from Dvl-1-overexpressing and αEcatenin knockout mice. In both cases, levels of active βcatenin increased because of liberation from the destruction complex and adherens junction, respectively.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
“…This observed phenotype was rescued by pharmacological inhibition of the transcriptional function of β‐catenin. The in vivo silencing of Pygo1 also attenuates the development of isoproterenol‐induced heart hypertrophy 187 . More evidence of the hypertrophic action of β‐catenin comes from Dvl‐1‐overexpressing and αE‐catenin knockout mice.…”
Section: β‐Catenin In Cardiogenesis Postnatal Heart Growth and Cardia...mentioning
confidence: 99%
“…Inhibitors of canonical Wnt signalling, such as Frizzled and Dkk-1, induce cardiac gene expression in the posterior lateral plate mesoderm (Marvin et al 2001 ). Our previous study showed that PYGO, which does not regulate the formation of adult cardiac valves, functions through canonical Wnt signalling (Lin et al 2021 ; Tang et al 2013 ). While investigating hUC-MSCs differentiation and cardiomyocyte-like cell formation, we adopted a different approach not used in other studies (Joshi et al 2018 ; Pham et al 2016 ; Ruan et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing reports indicate that histone modification and DNA methylation are involved in the occurrence and development of myocardial hypertrophy ( 37 , 38 ). The occurrence and development of cardiac hypertrophy is also accompanied by the abnormal activation of a large number of important signaling pathways ( 5 , 39 , 40 ). Consequently, there is an increased level of interest in how key signaling pathways participate in the epigenetic regulation of cardiac hypertrophy ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%